Tuberculosis of the Gallbladder: An uncommon Case Report (Faridpur Medical College Journal, 2021)
Isolated gall bladder tuberculosis (GBTB) is exceedingly rare even in an endemic region and is usually found as a GB mass in association with cholelithiasis. Confirmed preoperative diagnosis is very difficult, and most cases are diagnosed after cholecystectomy. We present a case of a 45-years-old woman who came with symptoms of chronic cholecystitis. Computed tomography scan revealed intraluminal gallbladder mass and cholelithiasis. The patient underwent open cholecystectomy and GBTB was diagnosed after histopathological examination. Histopathological examination should be done after all cholecystectomy operations.Faridpur Med. Coll. J. 2020;15(2): 106-107